Hypocalcaemia and convulsions. Issue 620 (June 1977) - Gupta, M. M.; Grover, D. N.
Abstract : Hypocalcaemia may manifest with tetany, convulsions and even status eqilepticus. Recognition of underlying hypocalcaemia in convulsions is mandatory because the fits may not be adequately controlled by anti-convulsant drugs which may also aggravate hypocalcaemia. Vitamin D, by relieving hypocalcaemia, reduces the frequency of convulsions and may even eliminate them.